Metode Penelitian Dan Pengembangan (Pengenalan Untuk Mengembangkan Produk Pembelajaran Bahasa Arab) - Purnama, Sigit (Universitas Alma Ata, 2013)
The development research could be a relatively new kind of Arabic educational/instructional study in Indonesia. The aim of this study to provide Arabic educational/instructional product that could bridge between researchers and practitioners (Arabic teachers). Therefore practitioners just implement the result of the study in their educational/instruction activities.The development was conducted in several steps, designing, producing, and evaluating. Designing process is the first step in the development which was done by identifying and determining the objective, the target, the matter and supporting component. The second process is production in which all collected and compiled materials were arranged to became the initial product. The next process is product evaluation which consisted of some steps; media and subject matter expert evaluation, one to one experiment, small group experiment, and field experiment. Theoretically its aim to provide any product needed by user (teachers or students). Keyword: Development research